PENGARUH WORK-LIFE BALANCE, KONFLIK KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI RUTAN KELAS IIB BATURAJA - M. Bayu Zulian; Yuniarti Anwar; Harby R. Wiralaga (Journal Economics Technology And Entrepreneur, 2026)
This study aims to examine the influence of work-life balance, work conflict, and work stress on the work productivity of employees at the Class IIB Baturaja State Detention Center. The study employed a quantitative approach using multiple linear regression analysis. The analysis produced the regression equation Y = 4.852 + 0.330X? + 0.424X?, with a correlation coefficient of 0.424, indicating a moderate positive relationship. The coefficient of determination (R² = 0.275) indicates that the three independent variables explain 27.5% of the variation in employee work productivity, while the remaining 72.5% is influenced by other factors outside the scope of this study. Partial hypothesis testing revealed that work-life balance and work stress have a positive and significant effect on work productivity, whereas work conflict does not have a significant effect. Simultaneous hypothesis testing demonstrated that work-life balance, work conflict, and work stress collectively have a significant effect on the work productivity of employees at the Class IIB Baturaja State Detention Center, indicating that the proposed research model is appropriate for explaining the relationships among the variables examined.